Driver Acceptance of Adaptive Cruise Control and Active Lane Keeping in Five Production Vehicles. (September 2017) - Reagan, Ian J.; Kidd, David G.; Cicchino, Jessica B.
Little is known about how consumers interact with driving automation technology that controls steering, speed, or headway in production vehicles. Forty-eight Insurance Institute for Highway Safety employees used a Honda Civic, Infiniti QX60, Toyota Prius, or Audi A4 or Q7 as a personal vehicle for up to several weeks and completed surveys about their experiences. Agreement about whether adaptive cruise control (ACC) or active lane keeping (ALK) improved driving experience varied significantly among vehicles. The Q7's ACC improved the driving experience significantly more than its ALK. The Civic's ALK improved the driving experience more than the Q7's system, but this effect only approached significance. Drivers were most comfortable using systems on free-flowing interstates and least comfortable using ACC in stop-and-go traffic and ALK on curvy roads. The findings show a range of qualitative differences in driving automation technologies and that use of current technologies likely is limited to low-demand conditions.